Discovery of a sushi domain-containing protein 2-positive phenotype in circulating tumor cells of metastatic breast cancer patients - Bartkowiak, Kai; Mohammadi, Parinaz Mossahebi; Nissen, Paula; Werner, Stefan; Agorku, David; Andreas, Antje; Geffken, Maria; Peine, Sven Oliver; Verpoort, Karl; Deutsch, Thomas M.; Michel, Laura L.; Schneeweiss, Andreas; et al. (Scientific reports, 2025)
Cell lines derived from circulating tumor cells (CTCs) in the blood provide important biological information on cancer metastasis. CTC-ITB-01 is a CTC cell line derived from a patient with metastatic estrogen receptor-alpha (ER-alpha) positive breast cancer two months before the death of the patient. After a LC-MC/MS based proteomics analysis of CTC-ITB-01, we found extraordinary high levels of the poorly characterized protein SUSD2 (sushi domain-containing protein 2) in CTC-ITB-01. Expression of SUSD2 on subsets of CTCs was validated on clinical blood samples of patients with metastatic breast cancer. SUSD2-positive CTCs could be captured specifically by a MACS-based approach. We overexpressed SUSD2 in the poorly-metastatic cell line MCF-7. This resulted in upregulation of ER-alpha, the tumor progression protein GRP78 (78-kDa glucose-regulated protein) and downregulation of the tumor suppressor protein PDCD4 (programmed cell death protein 4). We observed downregulation of SUSD2 and PDCD4 after hypoxia and simulation of re-oxygenation in the blood in MCF-7 and MDA-MB-468, while in CTC-ITB-01 SUSD2 levels remained unchanged, and only PDCD4 was downregulated under hypoxia. In conclusion, we show, for the first time, that SUSD2 is expressed in CTCs and appears to affect key proteins in tumor progression and survival.